Sexual and reproductive health services (SRHS) for adolescents in Enugu state, Nigeria: a mixed methods approach - Amelia Ngozi ODO; Efiong Sunday SAMUEL; Evelyn N. NWAGU; Petra Obioma NNAMANI; Chiemezie S. ATAMA (BMC, 2018)
Abstract Background Availability and accessibility of sexual and reproductive health services for adolescents are very crucial for prevention and control of sexual and reproductive health problems. These services also play vital roles in the promotion of adolescents' sexual and reproductive health generally. The main purpose of the study was to determine the availability and accessibility (geographical and financial) of sexual and reproductive health services (SRHS) among adolescents in Enugu State, Nigeria. Methods A mixed methods approach was adopted for the study. 192 health facilities were reached to check availability of SRH services. Randomly sampled 1447 adolescents (12-22 years) completed the questionnaire correctly. Twenty-seven interviews and 18 group discussions were conducted. Instruments for data collection consisted of a checklist, a questionnaire, a focus group discussion guide and an in-depth interview guide. All instruments were pre-tested. Quantitative data were analyzed using descriptive statistics and Chi-square tests. NVivo 11 Pro software was used to code and thematically analyze the qualitative data. Results A total of 1447 adolescents (between 12 and 22 years) completed the questionnaire correctly. Among these adolescents, males constituted 42.9% while females were 57.1%. The majority (86.7%) of the adolescents reported availability of safe motherhood services, and 67.5% reported availability of services for prevention and management of STIs and HIV and AIDS. The majority reported that these services were geographically accessible but few were financially accessible to adolescents. However, qualitative data revealed that available services were not specifically provided for adolescents but for general use. Age (p = ≤ .05), education (p = ≤ .05) and income (p = ≤ .05) were found to be significantly associated with access to SRHS. Conclusion SRHS were generally physically available but not financially accessible to adolescents. Adolescents' clinics were not available and this could affect the access of SRHS by adolescents. Education and income were significantly associated with access to SRHS.